(untitled) (Modern education and development, 2025)
The clinical significance of donor-recipient incompatibility by erythrocyte antigens is dominant, since hemolysis is usually accompanied by organ and functional disorders of varying severity. It is no coincidence that the majority of erythrocyte antigens were discovered when studying the cause of PTO or hemolytic disease of the newborn (HDN) due to allo-sensitisation of a woman by fetal erythrocytes inherited from the father [1,2,3].